The Future of Education in Libya: Weighing the Pros and Cons of AI Integration - Sana Shrif,; Mona Jamoum, (AlQalam Journal of Medical and Applied Sciences, 2025)
The integration of Artificial Intelligence (AI) in education is progressively transforming teaching, learning, and administrative practices globally, with significant potential for application in Libya. the purpose of this research is to discuss and evaluate the benefits and risks of AI in the education system of Libya. To achieve this, a descriptive research approach was employed, using a questionnaire distributed to a selected group of educational professionals in Libya. The sample consisted of 1,000 participants, and the survey was conducted via the WhatsApp application. The results highlight that personalized learning received the highest mean score of 4.19, indicating strong agreement on its effectiveness. Automation of administrative tasks (mean 3.80) and data-driven decision-making (mean 3.98) also showed favorable perceptions, with low variances around 0.24–0.25, reflecting consistent responses. Improved student engagement had a mean of 3.91 and a standard deviation of 0.49, similar to others, suggesting overall positive and uniform attitudes. Additionally, most responses clustered around neutral to moderate agreement, with modes of 3 or 4, showing balanced or mildly supportive opinions. Variance values ranging from 1.39 to 1.48 suggest a moderate spread, indicating some disagreement among participants. Standard deviations around 1.18 to 1.21 confirm a consistent yet moderate level of variability, without extreme polarization The obtained results show strong agreement on the benefits of educational innovations, especially personalized learning, which had the highest mean, and all aspects scored highly with low variability, indicating consistent positive perceptions. At the same time, the conclusions reveal moderate concern among respondents about the cost and inequality issues related to AI in education, with variance and standard deviation values reflecting a consistent spread of opinions. This research contributes to the academic discourse on the impactful integration of AI in academic institutions and establishes positive perceptions for continual enhancement. Overall, funding infrastructure emerges as the most pressing challenge, with general agreement across participants.